Chronotype, sleep quality, impulsivity and aggression in patients with borderline personality disorder and healthy controls - Taşdelen, Yasin; İnaltekin, Ali (Informa UK Limited, 2024)
Impulsivity, aggression, and suicide are the major clinical symptoms of borderline personality disorder (BPD). Although previous studies indicated poor sleep quality and its relationship with clinical symptoms in patients with BPD, chronotype, an important sleep parameter, was not investigated in these patients. This study aimed to analyze chronotype and its relationship with clinical symptoms in patients with BPD. Participants in this study consisted of 68 BPD patients and 65 healthy controls. Subjective sleep characteristics, impulsivity, aggression, suicide probability, and chronotype were assessed using the Pittsburgh Sleep Quality Index (PSQI), Barratt Impulsivity Scale, Buss-Perry Aggression Scale (BPAQ), Suicide Probability Scale, and Morningness - Eveningness Questionnaire, respectively. PSQI total and subscale scores subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, sleep disturbances, and daytime drowsiness were significantly higher in the BPD group (p < 0.001). There was a positive correlation between the PSQI total score and the BPAQ total score (r = 0.268, p = 0.027). The rate of evening type was significantly higher in the control group (p = 0.004). Suicide attempts and the subscale of suicide probability hopelessness, suicidal ideation, and negative self-evaluation scores were significantly higher in evening type BPD patients. (p = 0.017, p = 0.009, p = 0.001, p = 0.047). Sleep quality is associated with aggression, and the eveningness chronotype is associated with suicide. It may be useful to focus on sleep problems in treating BPD patients.
Keywords: Adult; Male; Sleep Wake Disorders; Chronotype; Circadian Rhythm; Suicidal Ideation; Aggression; Young Adult; Sleep Quality; Borderline Personality Disorder; Surveys and Questionnaires; Case-Control Studies; Impulsive Behavior; Humans; Female; Sleep